Analysis of anchor bolt stress characteristics in arch ring support of super-large underground powerhouse. Issue 2 (May 2020) - Wu, Hao; Liu, Jian; Zhang, Shujun; Zhao, Chunlin; Li, Xiuwen; Tian, Dongcheng
Abstract: Taking the surrounding rock deformation and bolt stress response characteristics during arch excavation of the left bank underground powerhouse of baihetan hydropower station as the research object, On the basis of the monitoring data of anchor stress, anchor rod stress response characteristics summarized as three types including "stepped", "one pull one press" and "load drop", and preliminary discussed the mechanism of bolt stress. The research results can provide important technical support for the reinforcement design of cavern in the following similar projects and have guiding significance for engineering practice.